Premium intraocular lens adoption: Insights from a national health insurance analysis - Chi-Ying Huang; Christy Pu; Chiun-Ho Hou (Journal of the Formosan Medical Association, 2025)
Background: This study explores the utilization patterns of premium and nonpremium intraocular lenses (IOLs) under Taiwan's National Health Insurance, given the potential out-of-pocket expenses incurred by cataract surgery patients. Methods: A cross-sectional, population-based analysis was performed on patients who underwent IOL implantation between 2016 and 2020. IOLs were categorized into nonpremium and premium, with the latter further divided based on function. Logistic and multinomial logistic regression analyses were employed to identify factors influencing IOL implantation, with data stratified by medical institute type, ownership, and patient demographics. Results: In total, 1,194,805 IOLs were implanted during the study period. The rate of premium IOL implantation was lower compared to non-premium IOL implantation. However, the adoption rate of premium IOLs increased more rapidly than that of non-premium IOLs. Specifically, the adoption rate for premium IOLs was 35.2% in 2016, rising to 42.6% in 2020. Patients receiving treatment in clinics were considerably more likely to use nonpremium IOLs than were those receiving treatment in medical centers (12.7% higher probability for clinics; P < 0.001). The implantation of higher-end premium IOLs was more prevalent in clinics than in other medical institutes. The prevalence of premium IOL implantation was higher in private hospitals than in public hospitals (odds ratio: 1.403; P < 0.001). Premium IOLs were more commonly implanted in younger patients with higher income levels and without relative contraindications. Conclusion: IOL selection is associated with both personal and institutional characteristics. These factors should be considered in public policy development aimed at regulating the IOL market within a universal health insurance framework.